Application of a New Validated HPLC-PDA Method for Simultaneous Determination of Curcumin and Melatonin in Hyaluronic Acid-Coated Nanoemulsions - Vieira,Edna S. (2020)
In this study, a high-performance liquid chromatography with photodiode array detector (HPLC-PDA) method was developed and validated to simultaneously determine curcumin (CUR) and melatonin (MEL) in hyaluronic acid-coated nanoemulsions, a novel targetable delivery system to CD44 receptors overexpressed in many types of tumors. Chromatographic analyses were performed in reversed phase mode using a mobile phase consisting of acetonitrile, methanol and 0.1% formic acid (35:15:50, v/v/v) at a flow rate of 1 mL min-1, and detection at 223 and 425 nm. The method was successfully validated according to the parameters of specificity, linearity, limits of detection (LOD) and quantification (LOQ), inter/intra-day precision, accuracy, and robustness. Linearity was demonstrated in the CUR and MEL concentration range of 0.5-20.0 µg mL-1 and 1.0-40.0 µg mL-1 (r > 0.999), respectively. Relative standard deviation (RSD) values for intra-day and inter-day precision were lower than 5%, and mean drug recovery varied from 94.91 to 98.33%. Mean drug content of 85.2 and 501.4 µg mL-1 and entrapment efficiency of about 80 and 20% were obtained for CUR and MEL, respectively. These results may be correlated to the differences in the drug solubility of these drugs in the oil and water phases of the nanoemulsion.